The form of Law and its structure (Società e diritti, 2016)
The existence of the society implicates that a human wish, expression of the collectivity,rules the relationships among the men that make part of it: the right defines contrastsher juridical spheres of the partners through a delimitation of the whole reality. In howmuch it has normative nature, the right constitutes a formal datum, that can becontrasted to that substantial of the society, on which comes to engrave. The juridicalform is the conceptual representation of the reality, it is the idea that represents thethings on their mutual relationships. Juridical reality is more properly neverthelessreserved to that formal aspects that are expression of categorical juridical norms andnot hypothetical, and therefore in degree to create a structure. As human work, theright is not identified with the moral norms, even if its finalities, of guarantee of theexistence of a social body, they are ethically valid.